2015
DOI: 10.3389/fnsyn.2015.00006
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental distribution of GABAB receptor-mediated currents along the somatodendritic axis of hippocampal principal cells

Abstract: Activity of cortical principal cells is controlled by the GABAergic system providing inhibition in a compartmentalized manner along their somatodendritic axis. While GABAAR-mediated inhibitory synaptic transmission has been extensively characterized in hippocampal principal cells, little is known about the distribution of postsynaptic effects of GABABRs. In the present study, we have investigated the functional localization of GABABRs and their effector inwardly rectifying potassium (Kir3) channels by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 67 publications
(109 reference statements)
4
45
1
Order By: Relevance
“…We think this is unlikely however, because we found that GABA B expression is the highest in the apical dendritic layers of ventral CA1 neurons compared with their dorsal counterparts. Activation of postsynaptic neuronal GABA B receptors (Bettler, Kaupmann, Mosbacher, & Gassmann, ) was shown to directly inhibit several types of voltage‐sensitive calcium channels and generate inhibitory postsynaptic potentials via G protein‐coupled inwardly rectifying K + (GIRK) channels (Chalifoux and Carter, ; Degro, Kulik, Booker, & Vida, ; Liu et al, ; Sun and Wu, ; Yang, Tadavarty, Xu, & Sastry, ). This suggests their greater contribution to a hyperpolarizing action of GABA A receptors, specifically in the VH.…”
Section: Discussionmentioning
confidence: 99%
“…We think this is unlikely however, because we found that GABA B expression is the highest in the apical dendritic layers of ventral CA1 neurons compared with their dorsal counterparts. Activation of postsynaptic neuronal GABA B receptors (Bettler, Kaupmann, Mosbacher, & Gassmann, ) was shown to directly inhibit several types of voltage‐sensitive calcium channels and generate inhibitory postsynaptic potentials via G protein‐coupled inwardly rectifying K + (GIRK) channels (Chalifoux and Carter, ; Degro, Kulik, Booker, & Vida, ; Liu et al, ; Sun and Wu, ; Yang, Tadavarty, Xu, & Sastry, ). This suggests their greater contribution to a hyperpolarizing action of GABA A receptors, specifically in the VH.…”
Section: Discussionmentioning
confidence: 99%
“…It is well 459 known that GABAB transmission is linked to K + conductance, and shows both increases 460 and decreases in conductance. GABAB has been shown to be strongly linked to Kir3 461 activity [24,35], which may be playing a role here. The other candidate that may 462 explain our findings is a change in the cationic HCN channels that contribute to the Ih 463 current.…”
Section: It Is Unclear Presently How Gabab Transmission During the Inmentioning
confidence: 93%
“…This shows the relationship between the dendritic synaptic input current and 341 the amount of that current that reaches the soma, across a range of synaptic responses 342 ( Figure 4B receptor-mediated activity. GABAA receptor density is greatest in the peri-somatic 369 region, while GABAB receptor density is more uniform, but greater in distal dendrites, 370 and highest in the s. radiatum, where Schaffer collateral synapses terminate on CA1 371 pyramidal neurons [16,24,25]. To test the hypothesis that GABAB-mediated 372 transmission was involved in the observed change in D-S coupling after HFS, we 373 examined LTP, E-S coupling, and D-S coupling in the presence of the GABAB receptor 374 antagonist CGP-54626 (CGP).…”
mentioning
confidence: 99%
“…A subset of recordings were performed in adult rats (9 cells, P50-P60) that confirmed that GABA B Rs minimally activate K + currents in SOM-INs ( Figure S1). Endogenous release of GABA activates only a proportion of the cells' GABA B R complement (L€ uscher et al, 1997;Degro et al, 2015). Therefore, we next measured whole-cell currents (I WC ) produced by the GABA B R agonist baclofen.…”
Section: Gaba B R-mediated Ipscs Are Small In Som-insmentioning
confidence: 99%